Extinction of experience: The need to be more specific. Issue 3 (23rd June 2020) - Gaston, Kevin J.; Soga, Masashi
Abstract: Extinction of experience, the progressive loss of human–nature interactions, may prove to be one of the key environmental concepts of our times. Not only does this loss reduce the important benefits that people gain from these interactions, but it may also undermine their support for pro‐biodiversity policies and management actions, and thus play an important role in shaping the future of biodiversity. Here, to help improve understanding, encourage a more consistent approach and highlight research gaps, we consider some of the key features of the concept of extinction of experience, contentions that these have caused and propose some solutions. We focus particularly on the importance of (a) the definition of nature employed; (b) whether direct or other human–nature interactions are considered; (c) the differences between the loss and the extinction of experience; (d) the timing of the loss of interactions that is considered and (e) the difference between human–nature interactions and human–nature experiences. Differentiating between narrow and broad senses of nature, between childhood and lifelong timings, and between interactions and experiences leads to a typology of eight different forms of extinction of experience. Such a classification can be useful for targeting research, furthering understanding of the processes and dynamics of the extinction of experience, and developing policies to reduce this phenomenon and minimize its negative consequences. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.